The importance of correct management in a 15-year-old boy with severe pulmonary arterial hypertension associated with patent ductus arteriosus - Dyahris Koentartiwi; Devi Albaiti Jannati; Ardhanis Ramadhanti; Heny Martini (Pediatric Sciences Journal, 2022)
Background: Pulmonary arterial hypertension (PAH) is a condition in which pulmonary vascular pressure increases and is associated with diverse diseases or aetiologies. In children, 50% of PAH cases are caused by congenital heart disease (CHD), especially due to large left-to-right shunts. Large systemic to pulmonary shunts may develop in PAH if left untreated or repaired late. PAH, when present, markedly increases morbidity and mortality in patients with CHD. Case presentation: We present a 15-year-old boy with a large patent ductus arteriosus (PDA) and severe pulmonary arterial hypertension. Catheterization under general anaesthesia was performed at the age of 16 years. We performed an acute vasoreactivity test (AVT), with the AVT result showing pulmonary arterial hypertension with high flow and low resistance. Transcatheter closure (TCC) of PDA was performed, resulting in no residual PDA. Meanwhile, the echocardiographic finding showed that there was still class II pulmonary arterial hypertension. We then gave heart failure medication and selective pulmonary vasodilator for 6 months. Post-treatment, pulmonary artery systolic pressure was significantly lower (TR Vmax 2.31 m/s, TR Max PG 21 mmHg, estimated PAP 24 mmHg). In this case, clinical evaluation, CXR, ECG, echocardiography, and cardiac catheterization data were presented with a review of the current guidelines regarding the management of paediatric patients with PAH associated with PDA. Summary: TCC of PDA is an option to treat pulmonary hypertension in PDA patients. Combined use of drugs and TCC PDA proves beneficially synergistic effect with better outcomes and may reduce mortality.